Construcción participativa de un producto audiovisual sobre las historias de vida de las mujeres victimas del desplazamiento forzado de la Asociación Solidaria por la Vida (2018)
This document collects two stories of women victims of forced displacement in Colombia in an audiovisual product produced, written and recorded by them with the support of the facilitator and director of this thesis. In addition, the structuring process of the project is shaped step by step and how the final product was arrived, also it contains the activities that were carried out to remember, heal and build a memory of what has been the Colombian armed conflict and how it has affected, mainly, the life of women in the social, economic and sexual aspects. On the other hand, the project was supported by the Asociación Solidarios por la Vida (Solivida), a foundation located east of the city of Santiago de Cali, Colombia, which receives victims of forced displacement in the country and instructs them for free in legal processes for the recognition of their status as victims and provides them with other services in the psychosocial and early childhood support area. From this foundation come the testimonies of the women who participated in the project and who ended up telling their stories of how they had been abused, displaced and even kidnapped in rural areas of the country. This is a work of degree to opt for the title of Social Communicator - Journalist in the Universidad Autónoma de Occidente in the modality of Pasantía Comunitaria in which students have the possibility of being integrated for at least six months to a foundation and support from the creation of projects and community work to the development of society